Electric users pay for peak hours - Pappas, Mike (Raton, NM Raton Range, 1988)
Columns written by Mike Pappas, owner of the Sweet Shop Restaurant, for the Raton Daily Range on a wide variety of topics, some historical, some current, some personal.
Newspaper Article by Mike Pappas
Master list item #: 50
File location is in the Raton File Cabinet
Keywords: Raton Public Service; Local History; Life and Customs; Electricity; Inflation costs; Raton, New Mexico